Technological upgrading and secondary innovation in the South African IT Industry - Motau, Thabitha (University of the Witswatersrand, Johannesburg, 2023)
Information technology (IT) plays a critical role in solving complex business tasks and enabling businesses to provide solutions and services to customers. Most businesses and governments are efficient because of technology. Because of technology, people can connect and communicate around the globe faster than they could during the days of letters. IT can enable a country, businesses, and society to adapt to changes around them. For a country that is afflicted by many challenges such as poverty, unemployment, and health care challenges, IT can resolve these challenges using technology in a way that will have a positive impact on the South African economy. Due to globalisation, South Africa now forms part of the global economy and relies on IT to participate and compete in this global market. For several years, South Africa has been ranked as the most technologically advanced and innovative country in Sub-Saharan African region by The Global Competitiveness Report (GCR). The purpose of this report is to explore how South African IT companies have used imported technology to achieved higher levels of technological capabilities enabling the companies to develop endogenous innovation and sustainable economic growth which has resulted in the high ratings by the GCR. Empirical research was conducted focusing on two South African IT companies. The study was conducted using semi-structured interviews consisting of managing directors and chief executive officers of these two companies focusing on market entry strategy, value proposition, business model innovation (BMI) and technological paradigms and future growth plans. An industry expert was also interviewed as the third source of data collection to achieve triangulation. The key findings of the study based on the data collected from the two companies and the industry expert, are that the South African IT companies have achieved technological upgrading that has produced endogenous innovation specific to certain industries with a focus on business model innovation. South African IT companies have strategically employed BMI as a valuable tool, allowing SMEs to navigate the trade-off ii between innovation costs and benefits. BMI involves the creation, delivery, and capture of new value by designing innovative products or services tailored to meet unmet local customer needs. This may include process innovation for enhanced efficiency, optimising product distribution, integrating new technologies, reconfiguring existing activities, providing managed services for day-to-day support, and exploring new partnerships. The emergence of new technologies has presented opportunities for novel partnerships and the redefinition of existing process and business model architectures. This adaptive approach is crucial for maintaining competitiveness in the market. Furthermore, the integration of emerging technologies serves as an avenue for capturing new customers and fostering the growth of new IT start-ups. This report presents a detailed account of strategies followed by the two case studies to build technological capabilities to produce endogenous innovation.
This research report is submitted to the graduate school of University of Witwatersrand, Wits Business School as part of the requirements to fulfil the degree of Master of Management in the field of Innovation Studies
Keywords: Technology; Secondary innovation; South African; IT Industry; Information technology (IT); UCTD; SDG-9: Industry, innovation and infrastructure